Improving Science Learning Outcomes by Applying Problem-Based Learning Model - Lalu Usman Ali; Wahyuni Wahyuni; Azmar Azmar; Jumawal Jumawal; Iin Mahlia Fitriana (Universitas Muhammadiyah Makassar, 2023)
This study aims to improve students' learning outcomes and figure out their responses to the application of the problem-based learning model in learning natural sciences. This study is a classroom action research. The subjects of this study were 16 students of class VII SMP Negeri 1 Gunungsari in the odd semester of the 2022–2023 academic year. This research was conducted in two learning cycles, with the stages in each cycle including planning, action, observation/evaluation, and reflection. The data collection was carried out using two instruments, namely tests in the form of a pre-test (cycle 1) and a post-test (cycle 2) to examine the student learning outcomes after implementing PBL and a questionnaire to find out the student responses to the application of PBL. The data that have been collected were then analyzed descriptively. Based on the data analysis, the results showed that after the application of the problem-based learning model, there was an increase of 60.2% in students' science learning outcomes. The average value of students' learning outcomes in cycle I was 33, while that of in cycle II increased to 83. In addition, students' responses are in the positive category. This study concluded that the application of the problem-based learning model could improve students' learning outcomes in class VII at SMP Negeri 1 Gunungsari.